Fiscal Policy Implications for Labor Market Outcomes in Middle-Income Countries - Stepanyan, Ara (IMF Working Papers; Working Paper ;, 2015)
Many governments have initiated public employment programs or expanded the existing ones in response to high unemployment. However, in many middle-income countries, a relatively large government coexists with persistently high unemployment. This paper explores the question of whether public employment gives rise to distortions in the labor market in the medium to long-run. Our findings do not provide any evidence that public employment reduces unemployment rate. The analysis in this paper shows that large public employment does significantly affect labor market outcomes in middle-income countries and leads to job destruction in the private sector. The extent of the impact is largely influenced by the degree of substitutability between public and private production and the size of the rents in the public sector.